2013
DOI: 10.4269/ajtmh.2012.12-0245
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices Related to Leptospirosis among Urban Slum Residents in Brazil

Abstract: Abstract. Leptospirosis disproportionately affects residents of urban slums. To understand the knowledge, attitudes, and practices regarding leptospirosis, we conducted a cross-sectional study among residents of an urban slum community in Salvador, Brazil. Of the 257 residents who were interviewed, 225 (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 17 publications
3
35
0
3
Order By: Relevance
“…Through these analyses, we found that Leptospira transmission in urban slums occurs due to the interaction of poverty, geography and climate. Our analysis of long-term prospective data confirms previous studies that identified socioeconomic and environmental risk factors but were limited by their retrospective design or limited follow-up [ 12 , 20 22 , 33 ]. Importantly, we found that among other mechanisms for environmental exposure, at-risk slum residents become infected with Leptospira through behaviors that lead to contact with contaminated soil and mud, mobilized most often by floodwater during heavy rain events.…”
Section: Discussionsupporting
confidence: 85%
“…Through these analyses, we found that Leptospira transmission in urban slums occurs due to the interaction of poverty, geography and climate. Our analysis of long-term prospective data confirms previous studies that identified socioeconomic and environmental risk factors but were limited by their retrospective design or limited follow-up [ 12 , 20 22 , 33 ]. Importantly, we found that among other mechanisms for environmental exposure, at-risk slum residents become infected with Leptospira through behaviors that lead to contact with contaminated soil and mud, mobilized most often by floodwater during heavy rain events.…”
Section: Discussionsupporting
confidence: 85%
“…Selection of the independent variables was based on literature reviews that identified factors that had been, or plausibly could be, associated with likelihood of rodent contact or risk of rodent-borne diseases (e.g., leptospirosis and hantavirus). These included socio-demographic factors (e.g., age, gender, education, and economic status), 9,14,15 behavioral factors (e.g., cultivationrelated tasks), environmental factors (e.g., home characteristics), 4 and cultural context factors (e.g., knowing of the existence of leptospirosis). 16 Of these independent variables, 19 were dichotomous and three were continuous.…”
Section: Methodsmentioning
confidence: 99%
“…These included socio-demographic factors (e.g., age, gender, education, and economic status), 9,14,15 behavioral factors (e.g., cultivationrelated tasks), environmental factors (e.g., home characteristics), 4 and cultural context factors (e.g., knowing of the existence of leptospirosis). 16 Of these independent variables, 19 were dichotomous and three were continuous. For each dichotomous variable, the comparison group is described first, followed by the reference group.…”
Section: Methodsmentioning
confidence: 99%
“…Residents of another urban slum in Salvador identified improving trash collection as necessary to control leptospirosis in their community and reported current payment for private trash collection service to avoid trash accumulation in their community or a willingness to pay for this service. Residents reported removing trash on a daily basis but identified that trash cans are >50 m from their homes (118). Leptospira interrogans and L. icterohaemorrhagiae are pathogens of severe diseases that may cluster in urban areas where trash accumulates (123) but are also found in rural households in peri-domestic open containers (debris found around the household areas including buckets, pails, jars, barrels, and old tires) (123).…”
Section: Urban Zoonosis Associated With Solid Wastementioning
confidence: 99%